A Multi-Emulation System - Lynning, Ejvind (DAIMI Report Series, 1976)
Experimental applications of microprogramming such as language machines, list processing or matrix operations include problems such as filing system and I/O handling, which are of no real interest to the experimenter. A multi-emulation system, that allows creation of sets of co-operating programs at the micro- and higher levels, which may run on different virtual processors, can free the experimenter from the irrelevant problems. This report describes such a multi-emulation system which is implemented on the department's experimental microprogrammable machine RIKKE-1. It furthermore compares the described system with alternative systems that support multiple emulators.